A New Masdevallia (Pleurothallidinae: Orchidaceae) from the White-Sand Forests of the Central Amazon, Brazil - Pessoa, Edlley M. (2022)
Masdevallia britoi, a new species in Masdevallia sect. Minutae, is described and illustrated from the central Amazon in Brazil. It is similar to M. wendlaniana but differs by shorter sepals that are internally white, shorter oblong petals with a delicate tooth near the middle, shorter lip with deltoid marginal folds near the middle and three-denticulate apex, and shorter ovary. The new species grows in the white-sand forests locally known with the name Campinaranas. We also provide an identification key for the species of Masdevallia from the Brazilian Amazon.